1992
DOI: 10.1128/jvi.66.4.2037-2045.1992
|View full text |Cite
|
Sign up to set email alerts
|

Class I major histocompatibility proteins are an essential component of the simian virus 40 receptor

Abstract: The class I molecules encoded by the major histocompatibility complex (MHC) present endogenously synthesized antigenic peptide fragments to cytotoxic T lymphocytes. We show here that these proteins are an essential component of the cell surface receptor for simian virus 40 (SV40). First, SV40 binding to cells can be blocked by two monoclonal antibodies against class I human lymphocyte antigen (HLA) proteins but not by monoclonal antibodies specific for other cell surface proteins. Second, SV40 does not bind to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…is believed to use MHC class I antigens as receptors [11,25]. Early morphological studies showed that class I antigens could be associated with small non-4.2.3.…”
Section: Phagocytosis 421 Clathrin-coated Vesiclesmentioning
confidence: 99%
“…is believed to use MHC class I antigens as receptors [11,25]. Early morphological studies showed that class I antigens could be associated with small non-4.2.3.…”
Section: Phagocytosis 421 Clathrin-coated Vesiclesmentioning
confidence: 99%
“…However, as relatively stable membrane domains, it was unclear how caveolae could offer a productive entry pathway for SV40. The related murine polyoma virus has also been reported to internalise via caveolae (Richterová et al 2001;Gilbert et al 2003;Liebl et al 2006), but, while SV40 employs the class I Major Histocompatability Complex as a receptor, murine polyoma virus interacts with sialyloligosaccharide receptors (Breau et al 1992;Stehle and Harrison 1996). Furthermore, murine polyoma virus binding to host cells induces an up-regulation of primary and early response genes that regulate particle internalisation (Zullo et al 1987;Glenn and Eckhart 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Many viruses utilize various receptors for attachment and entry into cells. The polyomavirus, simian vacuolating virus 40 (SV 40), binds to the MHC class I molecule at the cell surface [20], but the MHC molecule is not internalized into the cells together with SV 40 [21]. The ganglioside GM1 also binds to SV 40, and is mediated to transport the virus from the plasma membrane to the endoplasmic reticulum (ER), and a role of GM1 as a functional receptor has been suggested [22].…”
Section: Discussionmentioning
confidence: 99%